Reforming Public Institutions and Strengthening Governance : A World Bank Strategy Implementation Update - World Bank (Washington, DC, 2013)
The purpose of this report is to assess progress to date in implementing the World Bank's strategy for governance and public sector reform, Reforming Public Institutions and Strengthening Governance: A World Bank Strategy. It is organized according to the goals and commitments laid out in the Strategy itself, to allow readers to track to what extent the Strategy is being implemented. Part I synthesizes progress and issues across the Bank, while Part II highlights specific challenges and approaches of individual Regions, the Development Research Group, and World Bank Institute. The treatment of governance issues and the focus on institution building in Country Assistance Strategies (CASs) and Bank programs have increased steadily over the past four years. Almost all recent CASs diagnose the governance situation in the relevant country, and lending for governance and institution building has increased significantly. Operations Evaluation Department and Quality Assurance Group ratings indicate that the quality of the public sector portfolio has improved considerably and that the number of projects at risk has fallen.